Effects of information and communication technologies on the work-life balance of resident assistants - Winters, Danielle (Kansas State University, 2015)
Information and Communication Technologies, or ICTs (Golden, 2013) have become prevalent in the modern professional’s life. Clark (2000) uses work/life border theory to explain the ways in which individuals manage the so-called borders between personal and professional life, and this study applies work/life border theory to better understand the work-life balance perceptions of one particular group: university resident assistants (RAs). As RAs, the participants of this study face rather unique struggles in managing boundaries between personal life and private life, due to the fact that they live and work in the same physical locations. Results indicate that many RAs have adopted the use of ICTs, which allows them to leave the physical space of the dormitories. However, this study shows the fascinating double-bind such ICT-centered schedule management can create: although use of ICTs allows for schedule management and time away from the physical work-space of the dorms, RAs remain on-call and reachable at all times.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: Information and communication technologies; Work-life balance; Double-bind; Segmentation; Integration